Against ‘Enterprise’ (but not against ‘enterprise’, for that would make no sense) - du Gay, Paul (Organization (London, England), 2004)
This article explores different conceptions of ‘enterprise’ and seeks to indicate the extent to which they are non-reducible. Its main focus is on one particular conception of enterprise that has underpinned a powerful critique of public sector organizations and which has been translated into a variety of specific organizational strategies for restructuring or modernizing the public services. This conception, it is argued, is very different from that informing much of the prescriptive and descriptive literature on entrepreneurship within management studies, for instance. The article also attempts to question the opposition between ‘bureaucracy’ and ‘enterprise’ that frames this self-styled ‘entrepreneurial’ approach to organizational reform. This epochal ‘bureaucracy/enterprise’ dualism, it is argued, is best viewed as a rhetorical move in a political polemic, but one with real effects.